Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

DAMPs and PAMPs driven macrophage activation in kidney injury - Jia-hui Li; Zhu-jun Wu; Wan-ting Li; Chun-yin Lv; Li Wang; Rui-zhi Tan (Tissue and Cell, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Modulating local structural disorder in layered cathodes with alternating edge- and face-sharing octahedra for enhanced high-rate performance - Chengjun Fan; Xiaoxia Yang; Lingling Yao; Qin Wang; Xiao Ouyang; Leidang Zhou; Zhiwen Gao; Rui Jia; Xibang Chen; Jing Chen; Hao Liu; Bin Liao; et al. (Chemical Engineering Journal, 2026)

PbrSLAH3b mediates nitrate-dependent regulation of pollen tube growth in pear - Guodong Chen; Peng Cao; Jia Gao; Weitao Xiao; Cong Jing; Rui Cheng; Huijun Jiao; Jizhong Wang; Juyou Wu (Plant Science, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Relative-effect metrics do not reflect societal burden under population ageing: Evidence from cold spell–related dementia mortality in China - Rui Zhang; Songwang Wang; Yujie Meng; Huan Zheng; Zixiong Zhao; Qing Guo; Shuo Zhan; Qiang Chen; Chaonan Wang; Jia Zhao; Ainan Jia; Xuejie Du; et al. (Environmental Impact Assessment Review, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Recognition of kiwifruit pruning position based on vine segmentation and dormant bud detection with their planar distribution - Shuolin Kong; Bo Jia; Qichen Huang; Juncai Huang; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Dateng Zheng; Davut Karayel; et al. (Computers and Electronics in Agriculture, 2026)

Construction and mechanism interpretation of capillary model based on LNAPL migration kinetics - Ziyi Wu; Rui Zuo; Xianyuan Du; Zhenkun Xue; Ziqiu Nie; Jiawei Liu; Jie Yang; Haoyang Jia; Shengjie Hu (Water Research, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

A photoelectrochemical signal amplification mechanism with Exonuclease III driven stable generation of “Swing Arm” tetrahedral DNA walkers for mediating photogenerated carrier transfer - Jinjie Liu; Dongquan Leng; Yu Du; Tingting Wu; Dehao Jia; Lei Yang; Rui Xu; Qin Wei (Analytica Chimica Acta, 2026)

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Tuning the fate of radical intermediates: The pivotal role of catalyst acidity and texture in steering lignin pyrolysis pathways - Yuyang Fan; Chao Liu; Zhengxue Zhang; Shiliang Wu; Anqing Zheng; Zhaojuan Zheng; Jia Ouyang; Rui Xiao (Fuel, 2026)

A model-data synergy framework for assessing and enhancing runoff control in sponge cities: Sensitivity-driven calibration and multi-tiered monitoring integration - Guorui Wu; Jia Guo; Nan Ni; Suhui Wang; Songwen Yang; Rui Wang; Liang Feng (Ecological Modelling, 2026)

Response of anaerobic ammonium oxidation granular sludge to acute GenX exposure: Performance, microbial responses, and mechanistic insights - Xu-Ming Liu; An-Dong Zhao; Bai-Hang Zhao; Lei-Yue Wu; Rui-Xuan Liu; Peng-Biao Jia (Chemical Engineering Journal, 2026)

Effects of MFC-mediated iron tailings on heavy metals transformation and microbial communities during the aerobic composting of pig manure - Keping Li; Rui Yu; Xia Wu; Wencong Yang; Wenyue Shao; Yong Yu; Nana Luo; Jia Zhou (International Biodeterioration & Biodegradation, 2026)

Improved mitigation of reverse osmosis membrane biofouling via synergistic UV light-emitting diodes and chlorine disinfection - Yu-jia Gao; Rui-ning Wang; Shi-tong Yu; Ke-fan Cao; Xu-Cheng Cai; Yu Hong; Yun Wang; Wei E. Huang; Nozomu Ikuno; Nakata Koji; Hong-ying Hu; Yin-hu Wu (Desalination, 2026)

Carbonate-retaining multilayer Co(OH)2@FeOOH electrodes enable superior stability in seawater oxygen evolution: Sustaining 5000 h at 1 A cm−2 - Yingxia Wei; Zhangwei Li; Farhat Nosheen; Xueyan Wu; Rui Xue; Xingyun Li; Yan Lv; Jixi Guo; Dianzeng Jia (Chemical Engineering Journal, 2026)

Extracellular Vesicle-Associated MicroRNA-25-3p Derived from Pancreatic Cancer Cells Promotes Hepatic Stellate Cell Activation and Enhances Cancer Progression - Xuejiao Wu; Rui Shen; Zilin Yang; Yuming Tang; Jia Huang; Weiyan Yao (Biochemical Genetics, 2026)

Biomass-derived modifiers customize polymeric nanofiltration membranes for enhanced lithium/magnesium ion selectivity - Xin-Xi Ding; Cheng Jiang; Jia-Wang Wang; Zi-Hui Wu; Rui Luo; Yue Zhao; Yue Wang; Dan-Dan Shao (Desalination, 2026)

Unlocking closed-loop recycling of spent LiFePO4 batteries via photocatalytic leaching: Efficient lithium recovery and mechanistic insights - Yinzhuang Fang; Shuya Chang; Yurong Han; Yifeng Han; Lina Jia; Mingyang Wu; Xianbao Wang; Rui Xia; Tao Mei (Chemical Engineering Journal, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

SAA-YOLO: A scale-aware attention enhanced YOLOv10 for UAV-based detection of medicinal plant Phlomoides rotata in alpine grasslands - Rong Ding; Chenghui Wang; Xuemei Wu; Guopeng Chen; Jiangkai Yang; Hongmei Jia; Shihong Zhong; Rui Gu (Computers and Electronics in Agriculture, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Construction and textural modification of soft surimi gel from spanish mackerel (Scomberomorus niphonius) by polysaccharides - Yin-Yin Lv; Xian-Hao Zhang; Jia-Ni Zhou; Ying-Rui Wang; Zhu-Jun Zhang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Seismic resilience assessment of water treatment plants considering the damages and interdependencies of internal facilities - Benwei Hou; Rui Jia; Bin Wu; Liang Liu; Chengshun Xu (Soil Dynamics and Earthquake Engineering, 2026)

Soil organic matter revisited: Why humic substances still matter? - Sen DOU; Yifeng ZHANG; Jun SHAN; Meng WU; Rui MA; Song GUAN; Zhongjun JIA (Pedosphere, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Biaxially oriented polyethylene film packing and hydrogen sulfide fumigation maintain postharvest quality of tomato fruits by reducing malondialdehyde levels and water loss - Le-Ying Yan; Pedro Garcia-Caparros; Jia-Xin Wang; Wan-Ken Chen; Xiong-Jie Wu; Dong-Bo Zhu; Rui Zhang; Zhao-Zhong Wang; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2026)

Simulated Microgravity affects immune reaction to infection through altering lymphocyte differentiation, cytokine secretion, and macrophage polarization - Hongyan Cai; Rui Jia; Huimin Chen; Yingying Wu; Yaya Qin; Shaoyan Si; Lei Zhu; Xiaotong Lou; Xiangru Li (Life Sciences in Space Research, 2026)

Deciphering the effects of cascade reservoirs on phytoplankton communities in a karst river: Importance of super-large reservoirs - Jiang Wu; Xiao-Nan Wu; Xiao-Hui Zhao; Xu Han; En-Hang Liang; Rui An; Jia-Ju Liu; Wei-Ling Sun; Nan Xu; Ting Wang (Journal of Environmental Management, 2026)

Dietary Haematococcus pluvialis powder enhances the growth and hepatopancreas and intestinal health of Leuciscus waleckii via NF-κB/Nrf2 pathway - Bei Xi; Tong-Tong Tan; Qi Sun; Ming-Xuan Zhang; Jia-Jing Wang; Rui Zhu; Deng-Lai Li; Li-Fang Wu (Fish & Shellfish Immunology, 2026)

Molecular characterization, transcriptional profiling, and immune functional analysis of CD94 from Nile tilapia (Oreochromis niloticus) - Yijian Huang; Guoling Luo; Dandan Wu; Zhongxin Hu; Jia Cai; Bei Wang; Yishan Lu; Zhiwen Wang; Rui Song; Jichang Jian; Yu Huang (Fish & Shellfish Immunology, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Formation mechanism analysis of karst collapses in Geleshan Town-Zhongliang Town, Chongqing, China - Yuanbin Wu; Rui Cao; Jia Wang; Yan Meng; Renchao Yin; Zhikui Liu (Carbonates and Evaporites, 2025)

Prediction method of propeller tip vortex cavitation inception based on bubble dynamics models and change-point detection - Jia Duan; Rongwu Xu; Lilin Cui; Bin Ji; Rui Wu; Heng Liu; Chang Chen (Ocean Engineering, 2025)

Enhanced electrocatalytic oxidation of high-salinity quaternary ammonium compound wastewater using CNTs-(Ru Ir O2)/Ti Anode - Hao-Tian Liu; Han-Qing Zhao; Yi-Rui Yang; Shuang Wu; Jia-Ping Huang; Rui-Han Yu; Hongcheng Bai; Aqiang Ding; Daijun Zhang; Peili Lu (Journal of Environmental Sciences, 2025)

Dynamic response of ceramic-reinforced metallic corrugated sandwich structures under combined blast-fragment loading - Chang-ye Ni; Cong Luo; Lu-sheng Qiang; Xin-yi Bai; Jia-le Wu; Jian-hong Zhang; Rui Zhang (Engineering Structures, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Selective adsorptive separation of xylene isomers in vapor and liquid phases by nonporous adaptive crystals of leaning pillar[6]arenes - Yu-Xiang Sun; Susu Ren; Gengxin Wu; Xiang-Shuai Li; Haitao Wang; Jia-Rui Wu (Chemical Engineering Journal, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Iron and Ferritin Dyshomeostasis Intersect with Sex, Age, and Disease Severity in Amyotrophic Lateral Sclerosis - Xiaoge Xie; Peng Wu; Ting Wen; Rui Jia; Ronghua Zhang; Fangfang Hu; Jiaoting Jin; Xing Qin; Qiao Yi Chen (Journal of Molecular Neuroscience, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

A series of meroterpenoids with highly oxygenated skeletons from the endophytic fungus Penicillium sp. and their anti-inflammatory activities - Tu-Xiang Mo; Liu-Xia Lv; Xi-Shan Huang; Jia-Tong Zhou; Qian Wu; Xian-Hua He; Li-Qi Liang; Wei-Feng Xu; Jun Li; Rui-Yun Yang (Phytochemistry, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Wound healing accelerated by stem cell bandage - Yingying Liu; Aman Lv; Jinjie Wu; Xiaoyan Wang; Yang Liu; Pui-In Mak; Rui P. Martins; Ren-He Xu; Yanwei Jia (Chemical Engineering Journal, 2025)

Neuroprotective lindenane sesquiterpenoids from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Shan-Rong Luo; Qian-Qing Liu; Rui-Si Tang; Ning-Yu Chen; Di Luo; Lu Guo; Jia Li; Rui Wu; Zha-Jun Zhan (Phytochemistry, 2025)

Induction of immune priming against white spot syndrome in Procambarus clarkii through oral administration of transgenic Synechococcus sp. PCC7942: Insights from transcriptome analysis - Wei Liu; Xiaoping Chi; Max Peiyuan Wu; Yufeng Zhai; Rui Jia (Fish & Shellfish Immunology, 2025)

Linking gut microbiome profiles and white matter integrity to social behavior in young autistic children: from the perspective of individual variation - Xinyue Huang; Weixing Zhao; Rui Feng; Yuanyue Zhou; Jia Wang; Jinming Xiao; Lei Li; Xiaolong Shan; Yu Feng; Yating Ming; Jing Cao; Xiaodong Kang; et al. (Science Bulletin, 2025)

Wastewater surveillance for chronic disease drugs in wastewater treatment plants: Mass load, removal, and sewage epidemiology - Li Yao; Yang Hu; Jia-Hui Yang; Rui Wu; Fei-Long Chen; Xi Zhou (Journal of Hazardous Materials, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Tailoring porous carbon from optimized coal blends for high-performance supercapacitor electrodes - Yanli Zhu; Tao Wang; Yan Ma; Rui Sheng; Pengxu Ren; Jia Guo; Dianzeng Jia; Dongling Wu (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Lightweight, compressible and superhydrophobic coal-based nanofibrous/graphene oxide composite aerogel towards efficient oil and organic solvents adsorption - Yanchun Pei; Xueyan Wu; Zhichao Ren; Yan Lv; Rui Xue; Xin Luo; Jixi Guo; Dianzeng Jia (Desalination, 2025)

Unsteady hydrodynamic characteristics control of turbine blades by the vortex generators - Guotao Jia; Cong Chen; Lu Wang; Pengzhong Wang; Bin Huang; Rui Wu (Ocean Engineering, 2025)

Urinary concentrations of phthalate metabolites and the survival of high-grade serous ovarian cancer with advanced stage - Wen-Rui Zheng; Yi-Zi Li; Jin Xu; Ke-Xin Liu; Fang-Hua Liu; Wei-Yi Xing; Jia-Xin Liu; Lang Wu; Xiao-Ying Li; Dong-Hui Huang; Ting-Ting Gong; Qi-Jun Wu (Environmental Pollution, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Gelation melioration of clam Meretrix meretrix surimi based on the interactions with different plant/animal proteins - Lin-Da Zhang; Yue Liu; Ying-Rui Wang; Tian-Qi Zhou; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Gelation improvement of low-salt Chinese shrimp (Fenneropenaeus chinensis) surimi gel by L-arginine - Yue Liu; Lin-Da Zhang; Ying-Rui Wang; Tian-Qi Zhou; Yu-Qiao Wang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Spatial Characteristics of the Plasma Spark Source Wavelet - Jia Wei; Xiaozhu Hao; Jing Feng; Rui Yang; Lei Xing; Huaishan Liu; Wei Wang; Zhiqiang Wu; Dong Zhang; Linwei Li (Journal of Ocean University of China, 2025)

A new benzophenone derivative from Aspergillus fumigatus WJ-131 - Jia-Qi Liu; Sheng-Qi Zhang; Xiu-Hong Wu; Shuai-Xing Liu; Rui-Dang Yang; Liang Deng; Le Cai (Natural Product Research, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Dissecting the effect of substrate on polyamide reverse osmosis membranes via regulating substrate pore size by drying shrinkage - Rui Bai; Jin-Kai Qiu; Liu-Kun Wu; Zhen-Liang Xu; Cheng Lian; Hong-Lai Liu; Jia-Hui Li; Yong-Jian Tang (Desalination, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Factors influencing nonstandard piezocone dissipation curves and interpreting the coefficient of consolidation - Rui Jia; Zhongping Wu; Yiqun Li; Huayang Lei (Computers and Geotechnics, 2024)

MSC-mediated mitochondrial transfer restores mitochondrial DNA and function in neural progenitor cells of Leber’s hereditary optic neuropathy - Rui Wang; Feixiang Bao; Manjiao Lu; Xiaoyun Jia; Jiahui Xiao; Yi Wu; Qingjiong Zhang; Xingguo Liu (Science China Life Sciences, 2024)

Assessing the role of urban green infrastructure in mitigating summertime Urban Heat Island (UHI) effect in metropolitan Shanghai, China - Hao Zhang; Meng-yuan Kang; Zhen-ru Guan; Rui Zhou; Ai-lian Zhao; Wen-jia Wu; Hao-rong Yang (Sustainable Cities and Society, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

The role of pantothenic acid in alleviating hypoxia-induced liver injury of sub-adult grass carp (Ctenopharyngodon idellus): Possible mechanisms and implication - Yan Xia; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Jia-Yong Tang; Rui-Nan Zhang; Lu Zhang; Hai-Feng Mi; Lin Feng (Aquaculture, 2024)

HT-2 toxin impairs porcine oocyte in vitro maturation through disruption of endomembrane system - Jia-Rui Li; Si-Le Wu; Lin-Lin Hu; Bi-Yun Liao; Shao-Chen Sun (Theriogenology, 2024)

Efficient photocatalytic degradation of 24 imidazolium ionic liquids in an N-ZnO/simulated sunlight irradiation system and its mechanism - Jiaoqin Liu; Jingjing Zhang; Mengye Jia; Rui Ma; Ruijuan Qu; Zunyao Wang; Zhaoguo Liu; Yu Jiang; Haoxiang Zhang; Yujia Bai; Riya Jin; Yina Qiao; et al. (Chemical Engineering Journal, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

A multi-spatial scale analysis of anthropogenic nitrogen and phosphorus inputs in a large river basin: environmental effect and policy impact - Chenning Deng; Zeqian Zhang; Chaozheng Zhang; Rui Xu; Chong Nie; Qingjia Meng; Tiansen Zou; Hong Li; Jia Wu; Queping Yang (Regional Environmental Change, 2024)

Activation AMPK in Hypothalamic Paraventricular Nucleus Improves Renovascular Hypertension Through ERK1/2-NF-κB Pathway - Li-Yan Fu; Yu Yang; Rui-Juan Li; Abdoulaye Issotina Zibrila; Hua Tian; Xiu-Yue Jia; Jin-An Qiao; Jin-Min Wu; Jie Qi; Xiao-Jing Yu; Yu-Ming Kang (Cardiovascular Toxicology, 2024)

Regulating the electronic state of SnO2@NiFe-LDH heterojunction: Activating lattice oxygen for efficient oxygen evolution reaction - Chaojie Yin; Fanghe Zhou; Chunliang Ding; Shengde Jin; Rui Zhu; Jiang Wu; Wenhao Li; Wu Yang; Jia Lin; Xinxia Ma; Jinao Deng; Zhongjun Zhao (Fuel, 2024)

A novel AP2/ERF transcription factor, NtERF10, positively regulates plant height in tobacco - Li Xu; Yong Xu; Jia-rui Jiang; Chang-xin Cheng; Wen-wu Yang; Le-le Deng; Qi-li Mi; Wan-li Zeng; Jing Li; Qian Gao; Hai-ying Xiang; Xue-mei Li (Transgenic Research, 2024)
Ethylene response factors have been shown to be involved in the effects of plant developmental processes and to regulate stress tolerance. The aim of this study was to recognize the regulatory mechanisms of ethylene response factors on tobacco plant height. In this study, a gene-edited mutant (ERF10-KO) and wild type (WT) were utilized as experimental materials. Transcriptome and metabolome analyses were used to investigate the regulatory mechanism of NtERF10 gene editing on plant height in tobacco. Here, through the analysis of differentially expressed genes (DEGs), 2051 genes were upregulated and 1965 genes were downregulated. We characterized the different ERF10-KO and WT plant heights and identified key genes for photosynthesis, the plant hormone signal transduction pathway and the terpene biosynthesis pathway. NtERF10 was found to affect the growth and development of tobacco by regulating the expression levels of the PSAA , PSBA , GLY17 and GGP3 genes. Amino acid metabolism was analyzed by combining analyses of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). In addition, we found that members of the bHLH, NAC, MYB, and WRKY transcription factor families have vital roles in regulating plant height. This study not only provides important insights into the positive regulation of the ethylene response factor NtERF10 on plant height during plant growth and development but also provides new research ideas for tobacco molecular breeding.

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Genomic and transcriptomic analysis reveals the genetic diversity and adaptive signatures of Maduo sheep - Li-Na Chang; Xue Gao; Shi-Xin Wu; Rui-Dong Wan; Zhan-Xing Yang; Hai-Mei Zhao; Ke Zhang; Xin-Quan Zhao; You-Gui Fang; Gong-Xue Jia (Small Ruminant Research, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

Cytotoxicity sesquiterpenoids from the leaves of Datura stramonium L. - Juan Pan; Yan Liu; Ao-Fei Wang; Jia-Tong Wu; Rui Yang; Wei Guan; Adnan Mohammed Algradi; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2024)

Role and action mechanisms of miR-149 and miR-31 in regulating function of pig cumulus cells and oocytes - Jia-Shun Wu; Shuai Gong; Min Zhang; Rui-Jie Ma; Hui-Li Wang; Ming-Jiu Luo; Nan He; Jing-He Tan (Theriogenology, 2024)

The simultaneous removal of methylene blue (MB) and Ca2+ by recyclable adsorbents based the scales derived from coal gasification system - Bai-Hong An; Da-Mao Xu; Run-Ting Wang; Ye-Xuan Wen; Rui Geng; Jia-Yun Wu; Xian-Chun Tang; Hong-Bin Chen (Environmental Science and Pollution Research, 2024)

2D/2D ultrathin polypyrrole heterojunct aerogel with synergistic photocatalytic-photothermal evaporation performance for efficient water purification - Rui Li; Yong Li; Xiaohua Jia; Jin Yang; Xiao Miao; Dan Shao; Jun Wu; Haojie Song (Desalination, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Unraveling power-law scaling through exponential cell division dynamics - Jia-Xu Han; Zhuangdong Bai; Rui-Wu Wang (BioSystems, 2024)

Phenolic components from the fruits of Solanum xanthocarpum with anti-inflammatory activity - Yan Liu; Rui Yang; Hai-Dan Zou; Zhen-Peng Xu; Juan Pan; Jia-Tong Wu; Wei Guan; Zhi-Chao Hao; Adnan Mohammed Algradi; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2024)

Engineering extracellular electron transfer to promote simultaneous brewing wastewater treatment and chromium reduction - Deguang Wu; Baocai Zhang; Sicheng Shi; Rui Tang; Chunxiao Qiao; Teng Li; Jichao Jia; Meiyi Yang; Xiaoguang Si; Yifei Wang; Xi Sun; Dongguang Xiao; et al. (Journal of Hazardous Materials, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Facile synthesis of bead-chain structured MWCNTs@CeO2 with oxygen vacancies-rich for promoting electrochemical energy storage - Xiao-Man Cao; Jia-Qi Chen; Xin-Rui Zhao; Hao Ge; Daliang Liu; Qiong Wu; Zhi-Jia Sun; Qingguo Zhang (Chemical Engineering Journal, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

Roxarsone biotransformation by a nitroreductase and an acetyltransferase in Pseudomonas chlororaphis, a bacterium isolated from soil - Jie-wen Ma; Gui-wen Liu; Jia-Yu Zhai; Ke-qian Zhao; Ya-qing Wu; Rui-lian Yu; Gong-ren Hu; Yu Yan (Chemosphere, 2023)

Mechanistic insight into the adjuvant effect of co-exposure to ultrafine carbon black and high humidity on allergic asthma - Rui Deng; Jia Li; Haiping Wu; Mingpu Wang (Environmental Geochemistry and Health, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Application of enzymatically treated Artemisia annua L. on adult grass carp (Ctenopharyngodon idella): Improved growth performance, intestinal antioxidant capacity and apical junctional complex - Qin-Qin Dai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; He-Qun Shi; Lu Zhang; Hai-Feng Mi; Jia-Yong Tang; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Integrated insight into the molecular mechanisms of selenium-modulated, MPP+-induced cytotoxicity in a Parkinson’s disease model - Wen Liu; Feiyang Zhang; Wu Liang; Kaixin Huang; Chenguang Jia; Jie Zhang; Xiang Li; Wei Wei; Rui Gong; Jincao Chen (Journal of Trace Elements in Medicine and Biology, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

TRIM-containing 44 aggravates cardiac hypertrophy via TLR4/NOX4-induced ferroptosis - Leiming Wu; Meng Jia; Lili Xiao; Zheng Wang; Rui Yao; Yanzhou Zhang; Lu Gao (Journal of Molecular Medicine, 2023)

Heterogeneity of molecular-level and photochemical of dissolved organic matter derived from decomposing submerged macrophyte and algae - Jia He; Lixin Jiao; Guoqiang Zhi; Xue Wu; Yan Yang; Shuai Ding; Jinlong Zheng; Zhi Shao; Rui Xia (Journal of Environmental Management, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

Extreme cooling of 12.5 °C triggered by Typhoon Fungwong (2008) - Zhe-Wen Zheng; Jia-Yi Lin; Ganesh Gopalakrishnan; Yi-Rui Chen; Doon-Jing Doong; Chung-Ru Ho; Quanan Zheng; Chau-Ron Wu; Chen-Fen Huang (Ocean Modelling, 2023)

Morphological brain alterations in dialysis- and non-dialysis-dependent patients with chronic kidney disease - Huan Yu; Chaoyang Zhang; Yan Cai; Ning Wu; Xiuqin Jia; Jiaojiao Wu; Feng Shi; Rui Hua; Qi Yang (Metabolic Brain Disease, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Comprehensive analysis of the fates and risks of veterinary antibiotics in a small ecosystem comprising a pig farm and its surroundings in Northeast China - Jian-yong Wu; Jun-min Gao; Jin-song Guo; Xian-yu Hou; De-rui Wang; Jing-cheng Wu; Xiao-jun Li; Chun-yun Jia (Journal of Hazardous Materials, 2023)

Effects of calcination on the environmental behavior of sediments by phosphorus speciation and interface characterization - Rui Xia; Pingzhou Duan; Rui Li; Lixin Jiao; Jia He; Shuai Ding; Xue Wu (Journal of Environmental Management, 2023)

Molecular regulation of immunity in tea plants - Lu Rui; Jia-yi Su; Tao Li; Jia-miao Sun; Guang-heng Wu (Molecular Biology Reports, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Temperature-gradient-induced enhanced fog collection on polymer brush surfaces - Zheng-Hong Liang; Rui Feng; Jia-Min Wu; Dong Li; Fang Wang; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Regulation of Social Memory by Lateral Entorhinal Cortical Projection to Dorsal Hippocampal CA2 - Rui Dang; Yu Zhou; Yue Zhang; Die Liu; Miao Wu; An Liu; Zhengping Jia; Wei Xie (Neuroscience Bulletin, 2022)

Four new indole alkaloids from the roots of Isatis tinctoria - Dongdong Zhang; Yu Sun; Yanhong Shi; Ximin Wu; Qi Jia; Kaixian Chen; Yiming Li; Rui Wang (Natural Product Research, 2022)

Heavy metal pollution from copper smelting during the Shang Dynasty at the Laoniupo site in the Bahe River valley, Guanzhong Basin, China - Menglei Wu; Yana Jia; Yuzhu Zhang; Rui Wen; Jiahua Guo; Ninglian Wang; Wanqing Liu; Haijun Qiu; Haoyu Wang; Yiheng Xian; Chun Yu; Ting Yang (Journal of Geographical Sciences, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Association Between Serum Selenium Level and Subclinical Mastitis in Dairy Cattle - Di Wang; Daqing Jia; Ronghe He; Shuai Lian; Jianfa Wang; Rui Wu (Biological Trace Element Research, 2021)

Dynamic Response of Phragmites australis and Suaeda salsa to Climate Change in the Liaohe Delta Wetland - Yushu Zhang; Wenying Yu; Ruipeng Ji; Yijun Zhao; Rui Feng; Qingyu Jia; Jinwen Wu (Journal of Meteorological Research, 2021)

The geological characteristics of the large- and medium-sized gas fields in the South China Sea - Gongcheng Zhang; Dongdong Wang; Lei Lan; Shixiang Liu; Long Su; Long Wang; Wu Tang; Jia Guo; Rui Sun (Acta Oceanologica Sinica, 2021)

Indole alkaloid glycosides from Isatis tinctoria roots - Dongdong Zhang; Kang Du; Yitian Zhao; Songshan Shi; Yingchun Wu; Qi Jia; Kaixian Chen; Yiming Li; Rui Wang (Natural Product Research, 2021)

Experimental and numerical study on the load and deformation mechanism of a flexible net barrier under debris flow impact - Rui Jiang; Wen-ping Fei; Hong-wei Zhou; Miao Huo; Jia-wen Zhou; Jia-mei Wang; Jia-jun Wu (Bulletin of Engineering Geology and the Environment, 2020)

The characteristic of the synonymous codon usage and phylogenetic analysis of hepatitis B virus - Xiaoming Qi; Chaojun Wei; Yonghong Li; Yu Wu; Hui Xu; Rui Guo; Yanjuan Jia; Zhenhao Li; Zhenhong Wei; Wanxia Wang; Jing Jia; Yuanting Li; et al. (Genes & Genomics, 2020)
Background Hepatitis B virus (HBV) infection is a crucial medical issue worldwide. The dependence of HBV replication on host cell machineries and their co-evolutionary interactions prompt the codon usage pattern of viral genes to translation selection and mutation pressure. Objective The evolutionary characteristics of HBV and the natural selection effects of the human genome on the codon usage characteristics were analyzed to provide a basis for medication development for HBV infection. Methods The codon usage pattern of sequences from different HBV genotypes of our isolates and reference HBV genome sequences downloaded from the National Center for Biotechnology Information (NCBI) database were analyzed by computing the relative synonymous codon usage (RSCU), nucleotide content, codon adaptation index (CAI) and the effective number of codons (ENC). Results The highest ENC values were observed in the C genotypes, followed by the B genotypes. The ENC values indicated a weak codon usage bias (CUB) in HBV genome. The number of codons differentially used between the three genotypes was markedly higher than that of similarly used codons. High CAI values indicated a good adaptability of HBV to its host. The ENC plot indicated the occurrence of mutational pressure in the three genotypes. The mean Ka/Ks ratios in the three genotypes were lower than 1, which indicated a negative selection pressure. The CAI and GC3% plot indicated the existence of CUB in the HBV genome. Conclusions Nucleotide composition, mutation bias, negative selection and mutational pressure are key factors influencing the CUB and phylogenetic diversity in HBV genotypes. The data provided here could be useful for developing drugs for HBV infection.

Improvement of water quality in the Pearl River Estuary, China: a long-term (2008–2017) case study of temporal-spatial variation, source identification and ecological risk of heavy metals in surface water of Guangzhou - Yan-ping Zhao; Rui Wu; Jin-li Cui; Shu-chai Gan; Jia-chuan Pan; Peng-ran Guo (Environmental Science and Pollution Research, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Molecular mapping of the gene(s) conferring resistance to Soybean mosaic virus and Bean common mosaic virus in the soybean cultivar Raiden - Mian Wu; Ying-Na Liu; Cong Zhang; Xue-Ting Liu; Cheng-Chen Liu; Rui Guo; Ke-Xin Niu; An-Qi Zhu; Jia-Yin Yang; Jian-Qun Chen; Bin Wang (Theoretical and Applied Genetics, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Material Flow and Spatial Data Analysis of the Petroleum Use to Carbon Dioxide (CO 2 ) Emissions in Northeast China - Guang‐xin Liu; Ming Wu; Feng‐rui Jia; Qiang Yue; He‐ming Wang (Journal of Industrial Ecology, 2019)
Summary This study investigated the petroleum consumption and petroleum‐related CO 2 emissions (PCOEs) in Northeast China at city level using material flow analysis (MFA) and spatial data analysis (SDA). The petroleum flows for the year 2014 were plotted, and then the spatial patterns, weighted mean centers (WMCs), and spatial autocorrelations of petroleum consumption and PCOEs were calculated, respectively. It was found that Northeast China is a petroleum exploitation‐processing‐export region in China; the total input of petroleum flows comprised two parts—exploitation (about 60%) and import (about 40%). About one third of the total product oil supply flowed into other provinces. In the consumption process, the product oil was dominated by two sectors: the industry sector (45.5%) and the transportation sector (31%). The rate of PCOEs was 36.69 million tonnes in the waste discharge process. Meanwhile, the WMCs of the petroleum consumption and the PCOEs were located in the south of Northeast China. The location of the petroleum pipelines was the factor shown to determine the spatial patterns of petroleum consumption and PCOEs and the hotspots were distributed along the petroleum pipeline, especially in the Circum‐Bohai Sea regions. Economic development in these regions shows a positive dependence on petroleum consumption and generates larger PCOEs. The findings obtained in this study could provide important decision‐making support to low‐carbon development in Northeast China.

Dominant Synoptic Patterns and Their Relationships with PM2.5 Pollution in Winter over the Beijing-Tianjin-Hebei and Yangtze River Delta Regions in China - Yuzhi Liu; Bing Wang; Qingzhe Zhu; Run Luo; Chuqiao Wu; Rui Jia (Journal of Meteorological Research, 2019)

Anthropogenic Aerosol Pollution over the Eastern Slope of the Tibetan Plateau - Rui Jia; Min Luo; Yuzhi Liu; Qingzhe Zhu; Shan Hua; Chuqiao Wu; Tianbin Shao (Advances in Atmospheric Sciences, 2019)

Role of clouds in accelerating cold‐season warming during 2000–2015 over the Tibetan Plateau - Shan Hua; Yuzhi Liu; Rui Jia; Shuting Chang; Chuqiao Wu; Qingzhe Zhu; Tianbin Shao; Bing Wang (International Journal of Climatology, 2018)
With the global warming slowdown in the twenty‐first century, a huge discrepancy in regional climate warming has been identified over the main region of the Tibetan Plateau (TP). Compared with the +0.04 °C/decade warming from 1961 to 1999, the warming greatly accelerated for the period 2000–2015 at a rate of +0.30 °C/decade. During the same period, warming in the cold season (November to March) was more pronounced than in the warm season (May to September) over the TP. The results also indicated that the middle‐level cloud (middle cloud) decreased (−0.359%/year), while the high‐level cloud (high cloud) increased (+0.241%/year) over almost all the TP during the cold season. Further analysis showed positive net cloud radiative forcing over the western TP from 2000–2015, that is, a heating effect of clouds, especially in the cold season. Combining the trends of the increase in high cloud and the decrease in middle cloud over most parts of the TP, the decreased albedo effect of middle cloud and the increased longwave greenhouse effect of high cloud may have partially contributed to the sustained warming, especially in the cold season from 2000 to 2015. Meanwhile, the results showed that the warming rate and cloud area fraction changes were significantly amplified with elevation. The analysis based on a model of Coupled Model Intercomparison Project Phase 5 shows that the decreased middle cloud plays more important role than the increased high cloud in modulating the enhanced warming over the TP, especially in the cold season.

Ferroptosis, a Recent Defined Form of Critical Cell Death in Neurological Disorders - Jia-rui Wu; Qing-zhang Tuo; Peng Lei (Journal of Molecular Neuroscience, 2018)

An overview of the influence of atmospheric circulation on the climate in arid and semi-arid region of Central and East Asia - Yuzhi Liu; Chuqiao Wu; Rui Jia; Jianping Huang (Science China Earth Sciences, 2018)

Characterization of clinical features and outcome for human-to-human transmitted severe fever with thrombocytopenia syndrome - Bei Jia; Weihua Wu; Rui Huang; Guiyang Wang; Peixin Song; Yang Li; Yong Liu; Yali Xiong; Xiaomin Yan; Yingying Hao; Juan Xia; Zhaoping Zhang; et al. (Infectious Diseases, 2018)

Time is nothing: emotional consistency of autobiographical memory and its neural basis - Rui Xu; Juan Yang; Chunliang Feng; Haiyan Wu; Ruiwang Huang; Qiuli Yang; Zhihao Li; Pengfei Xu; Ruolei Gu; Yue-jia Luo (Brain Imaging and Behavior, 2018)

Re-engineering the two-component systems as light-regulated in Escherichia coli - Siya Ma; Siwei Luo; Li Wu; Zhi Liang; Jia-Rui Wu (Journal of Biosciences, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Reduction of soil-borne pathogen Fusarium solani reproduction in soil enriched with phenolic acids by inoculation of endophytic fungus Phomopsis liquidambari - Xing-Guang Xie; Chuan-Chao Dai; Xiao-Gang Li; Jia-Rui Wu; Qing-Qian Wu; Xing-Xiang Wang (BioControl, 2017)

Assessing spatial likelihood of flooding hazard using naïve Bayes and GIS: a case study in Bowen Basin, Australia - Rui Liu; Yun Chen; Jianping Wu; Lei Gao; Damian Barrett; Tingbao Xu; Linyi Li; Chang Huang; Jia Yu (Stochastic Environmental Research and Risk Assessment, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Phylogenetic analysis of Leymus (Poaceae: Triticeae) based on Random Amplified Polymorphic DNA - Yang-Yi Li; Ying-Xia Lei; Guan-Hui Chai; Gang Gao; Jia-Bin Deng; Yan Zhang; Shan-Shan Tong; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Rui-Wu Yang (Biologia, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

ZmDBF3, a Novel Transcription Factor from Maize (Zea mays L.), Is Involved in Multiple Abiotic Stress Tolerance - Wei Zhou; Cheng-Guo Jia; Xian Wu; Rui-Xue Hu; Gang Yu; Xiang-Hui Zhang; Jin-Liang Liu; Hong-Yu Pan (Plant Molecular Biology Reporter, 2016)

Predicting invasions of Wedelia trilobata (L.) Hitchc. with Maxent and GARP models - Zhong Qin; Jia-en Zhang; Antonio DiTommaso; Rui-long Wang; Rui-shan Wu (Journal of Plant Research, 2015)

Phylogenetic relationships among Elymus and related diploid genera (Triticeae: Poaceae) based on nuclear rDNA ITS sequences - Gang Gao; Jia-bin Deng; Xue-mei Gou; Qian Wang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2015)

A novel variant in the 3′ UTR of human SCN1A gene from a patient with Dravet syndrome decreases mRNA stability mediated by GAPDH’s binding - Tao Zeng; Zhao-Fei Dong; Shu-Jing Liu; Rui-Ping Wan; Ling-Jia Tang; Ting Liu; Qi-Hua Zhao; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Human Genetics, 2014)

Purification and photodynamic bioactivity of phycoerythrin and phycocyanin from Porphyra yezoensis Ueda - Chuner Cai; Yuan Wang; Chunxia Li; Ziye Guo; Rui Jia; Weining Wu; Yan Hu; Peimin He (Journal of Ocean University of China, 2014)

Association between interferon gamma +874 T>A polymorphism and acute renal allograft rejection: evidence from published studies - Yu-Zheng Ge; Ran Wu; Rui-Peng Jia; Hao Liu; Peng Yu; Yan Zhao; Yu-Ming Feng (Molecular Biology Reports, 2013)

Development of an immunochromatographic strip test for the rapid detection of okadaic acid in shellfish sample - Leqin Hu; Junxiu Liu; Qing Wang; Yang Zhang; Rui Jia; Chuner Cai; Weining Wu; Steven-Feng Chen; Peimin He (Journal of Applied Phycology, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Exogenous hydrogen sulfide attenuates diabetic myocardial injury through cardiac mitochondrial protection - Xin Zhong; Leihong Wang; Yuwen Wang; Shiyun Dong; Xiaoning Leng; Jing Jia; Yajun Zhao; Hulun Li; Xinying Zhang; Changqing Xu; Guangdong Yang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2012)

Impairment of liver regeneration by the histone deacetylase inhibitor valproic acid in mice - Qi Ke; Rui-na Yang; Feng Ye; Yu-jia Wang; Qiong Wu; Li Li; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2012)

A new QTL for resistance to Fusarium ear rot in maize - Zhi-Min Li; Jun-Qiang Ding; Rui-Xia Wang; Jia-Fa Chen; Xiao-Dong Sun; Wei Chen; Wei-Bin Song; Hua-Fang Dong; Xiao-Dong Dai; Zong-Liang Xia; Jian-Yu Wu (Journal of Applied Genetics, 2011)

Activity of the Antimicrobial Peptide and Thanatin Analog S-thanatin on Clinical Isolates of Klebsiella pneumoniae Resistant to Conventional Antibiotics with Different Structures - Guo-Qiu Wu; Jia-Xuan Ding; Lin-Xian Li; Hai-liang Wang; Rui Zhao; Zi-Long Shen (Current Microbiology, 2009)

Relationship between transmembrane signal transduction pathway and DNA repair and the mechanism after global cerebral ischemia-reperfusion in rats - Rong-Liang Xue; Jia-Xuan He; Ning Wang; Feng-Zhen Yao; Jian-Rui Lv; Gang Wu (Neuroscience Bulletin, 2009)